2012
DOI: 10.1007/s00430-012-0229-2
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral function and efficacy of polyvalent immunoglobulin products against CMV isolates in different human cell lines

Abstract: Primary infection and reactivation of human cytomegalovirus (CMV) remain a major problem in immunocompromised patients, frequently resulting in a life threatening CMV disease. Intravenous polyvalent (hyper)-immunoglobulins (IVIG) can be administered for therapy and prophylaxis of CMV infections. However, only limited data about the efficacy and mechanism of action of IVIG products against viral infections in vitro are available so far. In this study, the effect of IVIG on CMV infection in vitro was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Our findings that cell-cell spread into epithelial cells is resistant to neutralizing antibodies is in direct contrast with a large number of studies in which focus formation in epithelial cells was found to be highly sensitive to neutralizing antibodies (28,30,(32)(33)(34)39). To resolve this discrepancy, we performed focus expansion assays using the TB40-BAC4 strain of HCMV.…”
Section: -E)mentioning
confidence: 39%
See 1 more Smart Citation
“…Our findings that cell-cell spread into epithelial cells is resistant to neutralizing antibodies is in direct contrast with a large number of studies in which focus formation in epithelial cells was found to be highly sensitive to neutralizing antibodies (28,30,(32)(33)(34)39). To resolve this discrepancy, we performed focus expansion assays using the TB40-BAC4 strain of HCMV.…”
Section: -E)mentioning
confidence: 39%
“…Many current vaccine strategies are designed to induce a neutralizing antibody response (21)(22)(23)(24)(25)(26)(27). However, it is unclear whether the transmission of HCMV is sensitive or resistant to neutralization, potentially because many studies have used viruses that spread efficiently via the cellfree route (19,(28)(29)(30)(31)(32)(33)(34)(35)(36). To determine the neutralization sensitivity of Merlin, we tested a panel of antibody preparations.…”
Section: Significancementioning
confidence: 99%
“…The reported results of HCMV antibody treatment in patients differ very much between different studies. This might be explained by an inefficiency of HCMV antibody to block cell-tocell virus transmission in fibroblasts, different IgG preparations (38), and by differences between NK cells from different donors to mediate an ADCC effect (39). We demonstrated that NK92-CD16-158V cells had an enhanced effect on the control of HCMV transmission through ADCC.…”
Section: Discussionmentioning
confidence: 85%
“…Although IVIG usually has significant neutralizing antibody titers, we infer that during cyclic treatment IVIG suppresses intracellular HSV1 replication by an unknown mechanism(s) because HSV1 spreads exclusively via axonal transport in the PNS and CNS [35]. This is not without precedent as IVIG has been reported to inhibit HSV1 and HCMV plaque formation in monolayer cultures when added after virus is internalized [36,37]. Additionally, a pool of non-neutralizing monoclonal antibodies was shown to suppress growth of HSV1 in acutely infected Tgs cultured in vitro [38].…”
Section: Discussionmentioning
confidence: 99%